Betapa Indahnya Kedatangan Mereka Yang Membawa Berita Damai (Yesaya 52:1-12) - Dyulius Thomas Bilo (STT Pelita Dunia, 2018)
Abstract: It is interesting to study the phrase “how beautiful it is to come with them who bring messages of peace” in the context of the book of Isaiah. This sentence is appropriate to state how God is the savior and liberator for the Israelites who have been punished through exile and slavery to other nations. But in reality not everyone is able to understand the meaning of this expression. In its exploration, this paper aims to explain how the news of Israel's liberation from exile and slavery, how the state of the Israelites in exile and slavery, how God freed them, how beautiful the deliverance or salvation that God did for the Israelites, and how the correlation of Isaiah's message with Micah's message , Nahum, and the Apostle Paul, and how to interpret the expression